My computer likes me : when I speak in Basic - Albrecht, Bob, 1930- 4 0 16; 5 (Beaverton, OR : Dilithium, 1972)
A step-by-step guide to programming a computer using a beginning form of BASIC.
45785
Keywords: 2 -- 0; 6; Programming (Computers).;BASIC (Computer program language);BASIC (Computer language).;Computer programming; 20; 2